Tourism Focused on Vegans and Vegetarians - Jarossová, Malgorzata A.; Kašťáková, Elena (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2023)
Today, healthy lifestyles and environmental protection are coming to the fore. Increasingly, people want to protect both nature and their health and are changing the way they eat. Sometimes it is just trying something new, and sometimes it is a necessity caused by health problems. Veganism and vegetarianism are alternatives to the conventional way of eating. Veganism is one of the strictest forms of vegetarianism, which completely rejects the consumption of animal products. Vegans do not eat meat, dairy products, eggs, or honey. Veganism, however, is not just a change in diet. Its essence represents a whole philosophy of life that includes the protection of animal rights and the protection of the environment. Changes in diet on this scale can be difficult and can cause problems when travel ing. Veganism is a less explored area of tourism, but the rapid growth of the vegan and vegetarian movement observed in recent years requires a closer understanding of the topic. Catering, especially for vegans on a trip, can be very challenging. However, it is possible to eat healthy while traveling, it just takes more planning before the trip itself. The number of vegans and vegetarians is increasing every year around the world, which is a great opportunity for many companies, including transport companies. To target a product to vegans and vegetarians, it is essential to have a good understanding of these consumers, their habits, behaviours, requirements, and the factors that are important to that segment of consumers. The aim of this chapter is to introduce the reader to the topic of tourism aimed at vegans and vegetarians by indicating the European countries with the highest number of vegan and vegetarian restaurants, selected travel agencies aimed at vegan and vegetarian consumers, and giving examples of vegan/vegetarian menus offered by transport companies.
Jarossová, M. A. i Kašťáková, E. (2023). Tourism Focused on Vegans and Vegetarians. W: T. Lesiów (red.), Doskonalenie jakości usług przewodnickich w dobie pandemii (s. 17-32). Wrocław: Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu.
Keywords: tourism; vegans; vegetarians; food; travel; turystyka; weganie; wegwtarianie; jedzenie; podróże